2019
DOI: 10.1111/jbfa.12409
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐diverse boards and audit fees: What difference does gender quota legislation make?

Abstract: We investigate the effect of board (audit committee) gender diversity on audit fees in the French context. We also examine whether the relationship between the proportion of female directors and audit fees is moderated by the enactment of the gender quota law in 2011. We use the system GMM estimation approach on a matched sample of French firms listed in the SBF 120 index between 2002 and 2017. Consistent with the supply‐side perspective, we contend that female independent directors and female audit committee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 110 publications
(327 reference statements)
8
135
2
1
Order By: Relevance
“…The result conforms to the arguments of [45] as he stated that women do have better communicative skills and capabilities within and among different groups. The result also corroborates with the findings of [48,24,52] and [15] as they revealed in their studies that the presence of a mixed audit committee team (that is, mixture of both men and women) usually demands higher audit services from the external auditor thereby increasing the amount of audit fee. The result contradicts the findings of [46,47,24] and [13] where they revealed that the presence of women on audit committee structure would improve internal control and monitoring of management, reduce audit risk, thereby leading to reduction in audit fee.…”
Section: Random-effect Regression Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The result conforms to the arguments of [45] as he stated that women do have better communicative skills and capabilities within and among different groups. The result also corroborates with the findings of [48,24,52] and [15] as they revealed in their studies that the presence of a mixed audit committee team (that is, mixture of both men and women) usually demands higher audit services from the external auditor thereby increasing the amount of audit fee. The result contradicts the findings of [46,47,24] and [13] where they revealed that the presence of women on audit committee structure would improve internal control and monitoring of management, reduce audit risk, thereby leading to reduction in audit fee.…”
Section: Random-effect Regression Resultssupporting
confidence: 89%
“…The size of the bank can influence the amount an auditor would charge for providing audit service to its client because a bank with a large volume of transactions, receivables and customers scattered around the globe, can cause the work of the auditor to be rigorous, take more time to trace all the transactions, thereby resulting to more audit effort and time. This can subsequently lead to higher audit fee [33,4,28,47,1] and [52]. The bank size was measured through the natural logarithm of the sample banks.…”
Section: Materials Methods and Methodologymentioning
confidence: 99%
“…Oseni (2016) and Ullah, Pervaiz, and Zaefarian (2017) also observed that GMM controls the autocorrelation in the first and second differentiation and analyzed the more effective results in panel data study. For more refinement of the analysis, the Hansen and Sargan test was applied, which examines the reliability of the instrument and controls the overidentifying restrictions in the analysis (Jara et al, 2018;Nekhili et al, 2020).…”
Section: Econometric Equationmentioning
confidence: 99%
“…Subsequently, an effective AC is more likely to prevent management from making intentional or unintentional mistakes resulting in misleading stakeholders about firm economic performance (Dhaliwal et al., 2010). The literature also shows that AC financial expertise, AC independence levels, the frequency of AC meetings, and AC gender diversity have a positive influence on firms’ financial statement quality and internal controls quality (e.g., see more recent work by Anderson, Christ, Johnstone, & Rittenberg, 2012; Badolato, Donelson, & Ege, 2014, Bruynseels & Cardinaels, 2014; Nekhili, Gull, Chtioui, & Radhouane, 2019). Note that Appendix A summarises the key AC requirements as required by regulation (SOX), and highlights the key literature and findings.…”
Section: Ac Quality Financial Reporting and Internal Control Qualitymentioning
confidence: 99%